Psychodynamic interventions in cancer care I: psychometric results of a randomized controlled trial. Issue 1 (27th August 2013) - Ludwig, G.; Krenz, S.; Zdrojewski, C.; Bot, M.; Rousselle, I.; Stagno, D.; Luethi, F.; Leyvraz, S.; Stiefel, F.
Abstract Objective This study aimed to assess the effectiveness of psychodynamic interventions in cancer care. Methods Between 2006 and 2009, each consecutive outpatient of the Oncology Center of the University Hospital of Lausanne was invited to participate in a trial evaluating the effects of psychological support. Accepting patients were randomly assigned to an immediate intervention or a delayed intervention [4‐month waiting list]. Patients who declined support were asked to participate in an observational group [OG]. Socio‐demographic and medical data, anxiety, and depression [HADS], psychological distress [SCL‐90], alexithymia [TAS] and quality of life [EORTC] were recorded at baseline, and at 1, 4, 8, and 12‐months follow‐up. Results Of the 1973 approached patients, 1057 were excluded, 530 refused, and 386 were included with 196 of them participating in the OG. Of the patients in the intervention group [IG] [N = 190], 94 were randomized to the immediate intervention and 96 to the delayed intervention group (dIG). IG patients were younger, predominantly female, and had more psychological symptoms compared with those in the OG. Although patients of the IG and OG showed significant improvement in quality of life from baseline to 12‐months follow‐up, other outcomes [anxiety, depression, psychological distress, and alexithymia] remained unchanged. Conclusions The intervention was not effective with regards to psychometric outcome. The results have to be interpreted in light of the study design [untargeted intervention], the low levels of psychiatric symptoms, dropout of symptomatic patients, and the high prevalence of alexithymia. Copyright © 2013 John Wiley & Sons, Ltd.